Determinants and strategies of food security in smallholders' homegardens in Xiaoliangshan, SW China - Yi-Won Addi; Heping Liao; Xinan Chen; Mengran Li (Sustainable Futures)
This study examines the determinants of food security in smallholders’ homegardens in Xiaoliangshan, southwest China, through a mixed-methods approach combining field surveys, interviews, and spatial-statistical analyses. Key findings reveal that management time significantly enhances food security (explanatory power: 10.4 %, p < 0.01), suggesting that increased labor investment in homegardens directly improves household food availability. Similarly, livestock integration contributes an additional 7 % to food security outcomes (p < 0.01), underscoring its role in diversifying income and nutritional sources. Spatial heterogeneity is evident: proximity to markets strongly correlates with higher food security in accessible areas (explanatory power: 10.7 %, p < 0.01), implying that infrastructure development can amplify market access benefits, whereas self-sufficiency strategies dominate in remote zones, highlighting the need for localized support to strengthen subsistence practices. Region-specific effects of homegarden size and plant diversity further emphasize the importance of context-driven interventions. To enhance resilience, we recommend optimizing supply chains in connected regions, promoting self-reliance in isolated communities, and integrating modern technologies with traditional practices. While these insights advance strategies for equitable food security and contribute to global Sustainable Development Goals (SDGs), their broader applicability may require addressing complex socio-ecological dynamics beyond Xiaoliangshan’s localized context.